TINJAUAN PUSTAKA SISTEMATIS TENTANG IMPLEMENTASI MEDIA DIGITAL DALAM PEMBELAJARAN PJOK: TREN PENELITIAN, DAMPAK PEMBELAJARAN, DAN TANTANGAN PEDAGOGIS DI ERA TRANSFORMASI DIGITAL - Ilham Kamaruddin; Fhadil Nugraha; Aski Tenri Pakkua; Ukhwanul Atmawan Mantika; Bahtiar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to systematically examine the use of digital media in Physical Education, Sports, and Health (PJOK) learning through a qualitative approach with a Systematic Literature Review (SLR) design. A total of 25 national and international articles published between 2020 and 2025 obtained through Google Scholar and reviewed using PRISMA guidelines were used as sources of analysis. The results of the study indicate that the application of technologies such as E-Modules, interactive videos, and web-based applications has a significant impact on improving student learning outcomes in the cognitive, affective, and psychomotor domains. However, the implementation of digital media still faces major challenges in the form of infrastructure inequality and low teacher digital skills, which impact the gap in learning quality between urban and rural schools. Therefore, strategic planning is needed to improve educator’s digital literacy and develop technological competencies. Further research is recommended to focus on longitudinal studies to assess the long-term impact of digital media use on student learning outcomes and fitness, as well as strengthening infrastructure regulations and teacher training programs based on the DigCompEdu Framework.